Децентралізовані фінанси в сучасній фінансовій системі: розвиток та ризики - Кузнецова, Світлана Олександрівна; Писаковський, Антон Олексійович (Причорноморський науково-дослідний інститут економіки та інновацій, 2024)
Децентралізовані фінанси (DeFi) представляють важливий рух у сучасній фінансовій сфері, пропонуючи новий підхід до традиційних фінансових послуг. Використовуючи блокчейн, DeFi надає можливість доступу до фінансових операцій без посередників, що відрізняється від централізованих систем, де ключову роль відіграють банки та уряди. У цій статті розглядається розвиток та ризики DeFi, включаючи його перетворення на швидко зростаючу екосистему з мільярдами доларів у загальній заблокованій вартості (TVL). Основними принципами DeFi є відкритість, доступність та прозорість, що робить систему привабливою для глобальної аудиторії. Однак переваги DeFi супроводжуються ризиками. Волатильність криптовалют створює суттєві фінансові загрози, а складність смарт-контрактів може призвести до втрат через помилки користувачів. Відсутність регуляторного нагляду викликає занепокоєння щодо можливості шахрайства та незаконних дій у просторі DeFi. Незважаючи на виклики, технологічні інновації, такі як децентралізовані платформи кредитування та стратегії «yield farming», демонструють потенціал для зміни традиційних фінансових моделей. Проте швидкий темп розвитку індустрії також додає нових загроз, таких як вразливість протоколів та можливість системних збоїв. Тим не менш, подальший розвиток DeFi залежить від здатності поєднувати інновації з безпекою, а також балансувати децентралізацію з регуляторною відповідністю.

Decentralized fiance, known as DeFi, represents a signifiant movement in the modern fiancial sphere, offering a transformative approach to traditional fiancial services. By leveraging blockchain technology, DeFi opens up unprecedented opportunities for individuals and organizations to access fiancial services and operations in a decentralized manner. Unlike conventional fiancial systems, which rely on centralized institutions like banks and governments, DeFi operates on decentralized networks, enabling peer-to-peer transactions and fiancial contracts without the need for intermediaries. This article delves into the development and risks of DeFi in the contemporary fiancial system, examining how it has evolved from a niche concept into a rapidly growing ecosystem with billions of dollars in total value locked (TVL). The core principles of DeFi include openness, where anyone with an internet connection can participate; accessibility, where fiancial services are available to a global audience; and transparency, where transactions are recorded on public ledgers, ensuring accountability and reducing the risk of fraud. However, the advantages of DeFi are accompanied by signifiant drawbacks. The high volatility of cryptocurrencies, the primary assets used in DeFi, poses substantial fiancial risk to users. The complexity of smart contracts and decentralized applications (dApps) can be daunting for non-technical users, leading to potential losses due to user error. Furthermore, the lack of regulatory oversight raises concerns about the potential for fraud, money laundering, and other illicit activities within the DeFi space. In addition to the existing challenges, this article explores the opportunities for technology advancement and the creation of new fiancial products in the DeFi context. Innovations such as decentralized lending platforms, automated market makers (AMMs), and yield farming strategies have already demonstrated the potential to disrupt traditional fiancial models. However, the rapid pace of innovation also introduces new threats, such as the risk of protocol vulnerabilities, security breaches, and the potential for systemic failures in the DeFi ecosystem. The analysis of the fidings allows for a better understanding of the potential and limitations of DeFi in the modern fiancial system. As the DeFi landscape continues to evolve, it will be crucial for stakeholders, including developers, investors, regulators, and users, to carefully navigate the opportunities and risks presented by this emerging fild. Ultimately, the future of DeFi will depend on its ability to balance innovation with security, accessibility with complexity, and decentralization with regulatory compliance.
Decentralized finance in the modern financial system: development and risks
Keywords: децентралізовані фінанси; DeFi; технологія блокчейну; фінансова інновація; ризики; інновації; decentralized fiance; DeFi; blockchain technology; fiancial innovation; risks; innovations